Rheological, morphological, film and thermal properties of emulsions of polyvinyl acrylic resins, carboxymethyl cellulose and titanium oxide (2019)
The study of the physical-chemistry properties of dispersions are very importants in the coating industry, since of it depend the application and stability of these systems. Therefore, the aim of this investigation was evaluated the influence of the dispersion rate and titanium dioxide content in the rheological (steady and dynamic analyses), colloidal, morphological, films, and thermal properties of waterborne dispersions based on polyvinyl acrylic resin, carboxymethyl cellulose and titanium oxide. In this work were used two proportions of titanium oxide (5.51 wt% and 10.44 wt%) and the following dispersion rates: 900 rpm, 1200 rpm, 1500 rpm and 1725 rpm. The materials were characterized by rheological, dynamic light scattering, scanning electronic microscopy, adherence, hardness, flexibility and thermogravimetric analyses.